Hormonal receptors in mammary carcinoma: comparison between quantitative and qualitative methods - Montoro, Antonio Franco; Giannotti Filho , Osvaldo; Monteiro, Darcy Marchione; Montoro, Flávio Franco; Pinho, Maria Aparecida; Figueiredo, Marco Túlio Assis (São Paulo Medical Journal, 1997)
Alternatives to the traditional hormone receptor dosages for prognostic evaluation and clinical approach to breast cancer have been proposed for immunohistochemical determinations. For correlation purposes, such procedures were compared in 37 patients presenting 5 to 15 years of survival. Considering 30 fm/mg as the positivity index, the disagreement between both methods reached 35.1% with estrogen and 48.5% with progesterone receptors. When the positiveness level was changed to 20 fm/mg, the discrepancies were reduced to 32% with ER and increased to 57% with PgR. This study leads us to not recommend the immunohistochemical method applied to paraffin sections as an alternative procedure to the dextran-charcoal dosage for prognosis and therapeutic management of mammary carcinoma.